Staphylococcus aureus Small Colony Variants (SCVs): a road map for the metabolic pathways involved in persistent infections - Proctor, Richard A.; Kriegeskorte, André; Kahl, Barbara C.; Becker, Karsten; Löffler, Bettina; Peters, Georg (Frontiers in Cellular and Infection Microbiology, 2014)
Persistent and relapsing infections, despite apparently adequate antibiotic therapy, occur frequently with many pathogens, but it is an especially prominent problem with Staphylococcus aureus infections. For the purposes of this review, persistence will encompass both of the concepts of long term survival within the host, including colonization, and the concept of resisting antibiotic therapy even when susceptible in the clinical microbiology laboratory. Over the past two decades, the mechanisms whereby bacteria achieve persistence are slowly being unraveled. S. aureus small colony variants (SCVs) are linked to chronic, recurrent, and antibiotic-resistant infections, and the study of SCVs has contributed significantly to understanding of persistence. In our earlier work, defects in electron transport and thymidylate biosynthesis were linked to the development of the SCV phenotype (reviewed in 2006), thus this work will be discussed only briefly. Since 2006, it has been found that persistent organisms including SCVs are part of the normal life cycle of bacteria, and often they arise in response to harsh conditions, e.g., antibiotics, starvation, host cationic peptides. Many of the changes found in these early SCVs have provided a map for the discovery mechanisms (pathways) for the development of persistent organisms. For example, changes in RNA processing, stringent response, toxin-antitoxin, ribosome protein L6 (RplF), and cold shock protein B (CspB) found in SCVs are also found in other persisters. In addition, many classic persister organisms also show slow growth, hence SCVs. Recent work on S. aureus USA300 has elucidated the impact of aerobic expression of arginine deiminase genes on its ability to chronically colonize the skin and survive in abscesses. S. aureus SCVs also express arginine deiminase genes aerobically as well. Thus, many pathways found activated in electron transport type of SCVs are also increased in persisters that have intact electron transport. Many of these changes in metabolism result in slow growth; hence, small colonies are formed. Another common theme is that slow growth is also associated with reduced expression of virulence factors and enhanced uptake/survival within host cells. These adaptations to survive within the host are rooted in responses that were required for organisms to survive in a harsh environment long before they were mammals on the earth.